The Effectiveness of Web-based Inductive Learning Assisted on GeoGebra - Efrida Muchlis, Effie; Priatna, Nanang; Afgani Dahlan, Jarnawi (KnE Social Sciences, 2024)
This research used web-based inductive learning that facilitated plane geometry learning, where the learning was carried out online. It was hypothesized that students could learn the concept of plane geometry better when students were involved in the induction process with the help of GeoGebra software. They did explore with GeoGebra software to form several examples of the concept, testing the patterns that existed in the examples, and generalized the findings into new knowledge. With the help of the web and GeoGebra software, students could carry out their own learning and make their own discoveries. To test the effectiveness of web-based inductive learning, two classes were involved in the research, they were students of the Mathematics education study program Faculty of Teacher Training and Education, University of Bengkulu who took plane geometry class in the even semester of the 2021/2022 academic year as many as 68 students. This research was a quasi-experimental research with a post-test-only control group design. The instrument used for measurement was a description test. Based on the data analysis, it was found that the learning outcomes using web-based inductive learning assisted on GeoGebra were better than those using the expository method. Keywords: web, inductive learning, geogebra